Evaluasi Sistem Pengendalian Internal Atas Pembelian Bahan Baku Food and Beverage PT Tri Sukses Prima - La Ode Abdullah; Sania Indana Zulfa (Kajian Ekonomi dan Akuntansi Terapan, 2024)
This research aims to investigate the accounting information system employed by the company in the procurement of raw materials. Additionally, the study evaluates the implementation of internal controls by PT Tri Sukses Prima in its raw material procurement system located in Manguharjo District, Kota Madiun. The research employs a comparative descriptive analysis method with a quali-tative approach, and data is collected through field studies using an Internal Control Questionnaire (ICQ) as an analytical tool. The findings reveal that the internal control system for raw material procurement is largely in line with the internal control elements outlined by Mulyadi (2018). While PT Tri Sukses Prima effectively applies many of these control elements, there are still some areas needing improvement, such as overlapping job functions in the warehouse. Furthermore, based on the ICQ assessment, the internal control system for raw material procurement at PT Tri Sukses Prima is highly effective, with a score of 77.3%. Interpretation of these results shows that PT Tri Sukses Prima's commitment to strengthening its internal control has produced positive results. The effectiveness of implementing the Champion method not only increases operational efficiency but also ensures integrity and ac-countability in every raw material purchasing transaction.